Xây dựng chuỗi liên kết sản xuất – tiêu thụ nông sản thực phẩm theo hướng bảo đảm an toàn thực phẩm giữa thành phố Hồ Chí Minh và các tỉnh thành vùng Kinh tế Trọng điểm phía Nam - Trần Tiến, Khai; Lương Vinh Quốc, Duy; Phùng Thanh, Bình; Nguyễn Văn, Viên; Lê Văn Gia, Nhỏ; Trương Thanh, Vũ (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The Southern Key Economic Region has a large scale of agricultural and food trade to meet the needs of more than 20 million people. However, inner-regional connection for safe food supply and trade is still in difficulty when food chain is disjointedly managed by administrative boundaries. Therefore, it is necessary to find a regional linkage mechanism to solve food safety of supply chain in Ho Chi Minh City, other large cities, and agricultural production areas in the Southern Key Economic Region. This study uses qualitative approach, with various methods as surveys, interviews, seminars, case analysis, policy analysis to apply for the study of modern and traditional food supply chains in Ho Chi Minh City and other provinces in the region. The analytical information allows proposing a number of practical solutions for the development of regional linkage development policies to ensure food safety.